Conflict-Construing Metaphors in Nigerian Football Discourse - Oluremi, Tolulope Abisodun (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
This paper examines conflict-construing metaphors in Nigerian football discourse. Particular emphasis is placed on ascertaining metaphorical expressions, conceptualisations and the implicit experiential-ideology from a Cognitive Analysis approach with insights from Conceptual Metaphor Theory and Discourse Processing Theory. In the selected football discourse, a total of sixty news items were selected randomly from the online version of the Punch Newspaper, Kick Off and Complete Sports, covering a two-year time span:20 11 to 2012. On the basis of the identified metaphorical expressions, our findings reveal that sports journalists draw from our social memory of duel and war to conceptualise FOOTBALL IS A DUEL and FOOTBALL AS WAR. Thus, with the backgrounding of the fun associated with football, spectators and players tend to ensure victory since victory has nothing to do with fun.